2008
DOI: 10.3382/ps.2007-00512
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Mapping Quantitative Trait Loci for Body Weight and Abdominal Fat Traits: Effects of Marker Density and Sample Size

Abstract: Highly significant QTL for BW and abdominal fat traits on chicken chromosome 1 were reported previously in a unique F2 population. The objective of this study was to confirm and refine the QTL locations. Compared with the previous experiment, this study added 8 new families, including all the animals in the pedigree, and genotyped 9 more microsatellite markers, including 6 novel ones. Linkage analyses were performed. The results of the linkage analyses showed that the confidence intervals for BW and abdominal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 35 publications
1
37
0
1
Order By: Relevance
“…A number of studies reported significant QTL effects in the 167–179 Mb region of GGA1. Uemoto et al also detected QTL affecting BW42 and BW63 in 165–172 Mb on GGA1 [11], and QTL effects were also reported in these regions were associated with BW28–BW84, average daily gain, WW or BMW [2], [6], [7], [10], [11], [15]. Besnier et al reported a QTL for BW56 in the 169–175 Mb region of GGA1 with the most significant QTL effect at position 173,709,609 bp on GGA1 [35].…”
Section: Discussionmentioning
confidence: 96%
“…A number of studies reported significant QTL effects in the 167–179 Mb region of GGA1. Uemoto et al also detected QTL affecting BW42 and BW63 in 165–172 Mb on GGA1 [11], and QTL effects were also reported in these regions were associated with BW28–BW84, average daily gain, WW or BMW [2], [6], [7], [10], [11], [15]. Besnier et al reported a QTL for BW56 in the 169–175 Mb region of GGA1 with the most significant QTL effect at position 173,709,609 bp on GGA1 [35].…”
Section: Discussionmentioning
confidence: 96%
“…Growth is a very complex trait that is regulated by a number of genes and pathways, and more than 1500 quantitative trait loci have been found to be associated with chicken growth traits (Liu et al, 2008;Uemoto et al, 2009;Wahlberg et al, 2009;Gu et al, 2011). In the present study, 15 previously identified SNPs in GGA1 were detected using a custom Beadchip analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Generally speaking, a gain of information by more markers density resulted in smaller intervals, therefore, the application of additional markers is an effective way to increase QTL mapping resolution (Liu et al, 2008). The traditional markers such as SSRs and restriction fragment length polymorphism (RFLP) are not suitable when their linkage distance are zero and cannot meet the requirements of the high QTL mapping resolution.…”
Section: Discussionmentioning
confidence: 99%